Implementation of International Law of the Sea in Territorial Conflict Resolution: A Study in the Indo-Pacific Region - Shiddiqy, Muhammad Arsy Ash; Yuza, Ahmad Fitra; Wahab, Noorjima Abd (Universitas Teuku Umar, 2025)
The Indo-Pacific region has become the epicenter of global attention due to its abundant natural resources and strategic trade routes vital to the world economy. However, this potential is accompanied by frequent territorial conflicts arising from overlapping maritime claims among regional and major powers. These disputes not only threaten regional stability but also pose broader risks to international peace and maritime security. This study aims to explore and analyze the extent to which international law of the sea, particularly the United Nations Convention on the Law of the Sea (UNCLOS), is implemented in resolving territorial disputes within the Indo-Pacific region. The primary objective is to assess the effectiveness of UNCLOS as a legal instrument in guiding state behaviour and facilitating peaceful dispute settlement in complex geopolitical environments. Using a qualitative approach through comprehensive literature studies, the research examines the dynamics of conflicts and evaluates the performance of existing legal frameworks and dispute resolution mechanisms, including arbitration and negotiations under UNCLOS provisions. The findings reveal that although UNCLOS provides a solid legal foundation for defining maritime rights and obligations, its practical application often faces significant obstacles, including political interests, economic competition, and national security concerns that limit states' willingness to comply or cooperate. Moreover, the lack of enforcement mechanisms and the selective adherence to legal rulings further weaken the credibility of international law in the region. Consequently, the study emphasizes the need for stronger multilateral diplomatic efforts and cooperative regional frameworks to ensure fair and peaceful conflict resolution, thereby preventing further escalation in the Indo-Pacific.